Real-time PCR HPV genotyping in fine needle aspirations of metastatic head and neck squamous cell carcinoma: Exposing the limitations of conventional p16 immunostaining. (March 2019) - El-Salem, F.; Mansour, M.; Gitman, M.; Miles, B.A.; Posner, M.R.; Bakst, R.L.; Genden, E.M.; Westra, W.H.
Highlights: P16 staining is an unreliable HPV marker in FNAs of metastatic head and neck cancer. Real-time PCR is a highly reliable method for discerning HPV status in FNAs. HPV genotyping of FNAs may help refine the behavioral aspects of HPV-positive head and neck cancer. Abstract: Background: Given the propensity for HPV-positive head and neck squamous cell carcinoma (HPV-HNSCC) to metastasize to cervical lymph nodes, fine needle aspiration (FNA) plays an important diagnostic role in their initial detection. Indeed, there is now an unwavering commitment to HPV testing of FNAs even in the absence of clear methodologic guidelines and threshold criteria. A particular difficulty pertains to the interpretation of p16 staining. Design: Data was collected for 210 patients with suspected regionally metastatic HNSCC that had undergone FNA as part of standard clinical care. Initial HPV screening was performed on cell blocks with real-time PCR using primers targeting L1 of high-risk HPV types. Additional genotyping was performed on HPV-positive cases. The results were compared to p16 staining and subsequent excisions when available. Results: Of the 207 samples with sufficient DNA, 175 (85%) were HPV positive. HPV-16 was the most commonly detected genotype (90%). Of the HPV-positive cases, the primary site was the oropharynx (n = 154, 88.0%), supraglottic larynx (n = 2, 1.1%), nasal cavity (n = 1, 0.6%), hypopharynx (n = 1, 0.6%) or unknown (n = 17, 9.7%). On comparison with 31 paired surgical excisions, HPV status was concordant in all cases (100% correlation). Of 142 HPV-positive cases with matching p16 stains, p16 staining was reported as positive (n = 85, 60%), focal (n = 27, 19%), negative (n = 24, 17%) or non-contributory (n = 6, 4%); and only 33% reached the standard threshold limit (i.e. 70%) for HPV positivity. Conclusion: For patients with metastatic HNSCC, real-time PCR of FNAs reliably reflects HPV status, and is superior to conventional p16 immunostaining.